Synthesis, Biological Activity, and Mechanism of Action of 2‐Pyrazyl and Pyridylhydrazone Derivatives, New Classes of Antileishmanial Agents. (21st June 2018) - Coimbra, Elaine S.; Antinarelli, Luciana M. R.; de A. Crispi, Mariana; Nogueira, Thais C. M.; Pinheiro, Alessandra C.; de Souza, Marcus V. N.
Abstract: In this work, we report the antileishmanial activity of 23 compounds based on 2‐pyrazyl and 2‐pyridylhydrazone derivatives. The compounds were tested against the promastigotes of Leishmania amazonensis and L. braziliensis, murine macrophages, and intracellular L. amazonensis amastigotes. The most potent antileishmanial compound was selected for investigation into its mechanism of action. Among the evaluated compounds, five derivatives [( E )‐3‐((2‐(pyridin‐2‐yl)hydrazono)methyl)benzene‐1, 2‐diol (2 b ), ( E )‐4‐((2‐(pyridin‐2‐yl)hydrazono)methyl)benzene‐1, 3‐diol (2 c ), ( E )‐4‐nitro‐2‐((2‐(pyrazin‐2‐yl)hydrazono)methyl)phenol (2 s ), ( E )‐2‐(2‐(pyridin‐2‐ylmethylene)hydrazinyl)pyrazine (2 u ), and ( E )‐2‐(2‐((5‐nitrofuran‐2‐yl)methylene)hydrazinyl)pyrazine (2 v )] exhibited significant activity against L. amazonensis amastigote forms, with IC50 values below 20 μm . The majority of the compounds did not show any toxic effect on murine macrophages. Preliminary studies on the mode of action of members of this hydrazine‐derived series indicate that the accumulation of reactive oxygen species (ROS) and disruption of parasite mitochondrial function are important for the pharmacological effect on L. amazonensis promastigotes. Abstract : Hope against Leishmania parasites : In this work, the antileishmanial activity of 23 compounds based on 2‐pyrazyl and 2‐pyridylhydrazone derivatives was evaluated. Among the evaluated compounds, five derivatives exhibited significant activity against L. amazonensis amastigote forms, with IC50 values below 20 μm . The majority of the compounds did not show any toxic effect on murine macrophages.